One cell–one immunoglobin. Origin of limited heterogeneity of myeloma proteins - Awdeh, Z. L. (1970)
Plasma-cell tumour 5563 forms a single molecular species of immunoglobulin IgG(2)a, i.e. one variant of heavy chain and one variant of light chain. The molecules formed are labile and undergo alterations in charge properties, which rapidly lead to heterogeneity of the myeloma protein after synthesis. The single immunoglobulin species originally formed is found only after the shortest time-intervals tested, i.e. 10min incubation. Two types of changes in charge properties take place: (1) The originally formed protein (component o) is converted via an intermediate o′ into the most basic form of 5563 myeloma protein found in serum (component a). Charge differences between these components are suppressed at pH8.9, but can be studied by chromatography at pH6.5 or by analysis of isoelectric points by isoelectric focusing in polyacrylamide gel. The conversion of components o and o′ into component a apparently commences soon after assembly of the molecules and proceeds to completion extracellularly. (2) The second type of charge difference that distinguishes components a, b, c and d is exhibited over the pH range 6.0–8.9, but not at acid pH, and has been studied by electrophoresis at pH8.9, by chromatography and by isoelectric focusing. Conversion of component a into components b, c, d and e is only partial so that all five components can be found at decreasing concentrations in serum. Both types of charge alteration can be effected in vitro in the presence of serum, with optimum pH8.0. None of the charge differences could be attributed to the secretion process, since a component with the same isoelectric point as component o was found in secreted myeloma protein (1h). We have found no evidence to support the idea that the first type of change from component o to component a is due to ring formation of N-terminal [(14)C]glutamine into pyrrolid-2-one-5-carboxylic acid; however, our findings do not exclude this process happening very rapidly to a precursor of component o, possibly the polypeptide chain during or immediately after synthesis. In studying this point we noted that not only the heavy chains but also the κ-type light chain of mouse 5563 myeloma protein have a blocked N-terminus.